Abdul Kahar Muzakir: Bersama Emas dari Timur Jawa Menembus Pasar Internasional - Kharisma Rostia Fitri (Forum for Social and Humanities Studies, 2025)
Tobacco plantations in Jember began before 1850 along with other areas in the Dutch East Indies that planted commodities such as coffee, sugar cane, rubber, and indigo. In line with the changing politics and economy in the Netherlands, it provided opportunities for private companies to open businesses related to plantations. At that time, the tobacco plantation business grew rapidly thanks to the agrarian law of 1870 where the Dutch gave permission to entrepreneurs to manage land for 75 years. The commodities chosen at that time were commodities that had the potential for high selling value in the international market. Tobacco, which is the ingredient for making cigars, became a leading product from the Deli region in North Sumatra, Klaten in Central Java, and Besuki in East Java. The very profitable tobacco export process encouraged the growth of this industry and had a significant impact on economic growth in the area. In the 1800s, smoking cigars was a common habit, while cigarettes were still relatively rare at that time. A famous poem entitled "The Betrothed" by Rudyard Kipling was written in the early 20th century. Many people were made laborers in cigar factories before the mechanical manufacturing process became commonplace, because this industry was so vital. The history of cigars in Indonesia has a long journey. It began with the predecessor of a tobacco plantation named Deli Maatschappij in Deli, North Sumatra in 1869 which dominated the market for cigar wrappers or "wrappers". The method used in this study is a historical research method that includes several stages, namely Heuristics, which is the initial step in collecting data or historical sources, criticism, the second stage to test the validity of sources using external and internal criticism, interpretation, the third stage to give meaning to the sources that have been collected, Historiography, the last stage that focuses on writing history.